Preliminary results of pedestrian trainning systems for cherry production in the Rio Negro and Neuquen Valleys - Raffo Benegas, Maria Dolores (2021)
The need for increasing fruit industry competitiveness makes evaluation of production technology essential to reduce costs and to obtain fruit quality. The Kym Green Bush (KGB) system does not need support (lower cost of installation), plant vigor is controlled by dividing the axis into several temporary vertical ones, allowing the use of a wide range of rootstocks. The UFO (Upright Fruiting Offshoots) system shares the concepts of the KGB but has a supporting structure (posts, wires). The objective of this study was to evaluate the behavior of Lapins grafted onto SL64 and Pontaleb rootstocks, trained in the KGB, UFO and Central Axis (CA) systems. The trial was planted in 2014 at a distance of 2.5m × 4m (KGB and UFO) and at 2m × 4m (CA). Tree cultural practices were applied, and trunk cross sectional area, number of branches per tree, yield and fruit quality (size, soluble solids, titratable acidity, firmness and color) were measured. The KGB system was the easiest to implement and it gave the more vigorous plants in both combinations; the SL64 rootstock being more vigorous than Pontaleb. The KGB and UFO systems reduced winter pruning wages by 74 and 48%, respectively. Moreover, the Lapins/Pontaleb combination was more productive in all training systems. The KGB training system also allowed harvesting and pruning without the use of ladders.